A comparative study between propofol and etomidate in patients under general anesthesia - Aggarwal,Supriya (2016)
ABSTRACT BACKGROUND AND OBJECTIVES: Induction of anesthesia is a critical part of anesthesia practice. Sudden hypotension, arrhythmias, and cardiovascular collapse are threatening complications following injection of induction agent in hemodynamically unstable patients. It is desirable to use a safe agent with fewer adverse effects for this purpose. Present prospective randomized study is designed to compare propofol and etomidate for their effect on hemodynamics and various adverse effects on patients in general anesthesia. METHODS: Hundred ASA I and II patients of age group 18-60 years scheduled for elective surgical procedure under general anesthesia were randomly divided into two groups of 50 each receiving propofol (2 mg/kg) and etomidate (0.3 mg/kg) as an induction agent. Vital parameters at induction, laryngoscopy and thereafter recorded for comparison. Adverse effect viz. pain on injection, apnea and myoclonus were carefully watched. RESULTS: Demographic variables were comparable in both the groups. Patients in etomidate group showed little change in mean arterial pressure (MAP) and heart rate (HR) compared to propofol (p > 0.05) from baseline value. Pain on injection was more in propofol group while myoclonus activity was higher in etomidate group. CONCLUSIONS: This study concludes that etomidate is a better agent for induction than propofol in view of hemodynamic stability and less pain on injection.